Ten-Year Outcomes of Percutaneous Radiofrequency Ablation for Colorectal Cancer Liver Metastases in Perivascular vs. Non-Perivascular Locations: A Propensity-Score Matched Study - Jiang, Binbin; Luo, Hongjie; Yan, Kun; Zhang, Zhongyi; Li, Xiaoting; Wu, Wei; Yang, Wei; Chen, Minhua (Frontiers in Oncology, 2020)
Purpose: To compare long-term outcomes of percutaneous radiofrequency ablation for colorectal liver metastases in perivascular versus non-perivascular locations. Methods: This retrospective study included 388 consecutive patients with colorectal liver metastases (246 men, 142 women; age range 27–86 years) who underwent percutaneous radiofrequency ablation between January 2006 and December 2018. Propensity-score matching was performed for groups with perivascular and non-perivascular colorectal liver metastases. Rates of accumulative local tumor progression, overall survival, intra/extrahepatic recurrence, and complications were compared between the two groups. Results: We successfully matched 104 patients each in the perivascular and non-perivascular groups (mean age: 60.1±11.5 and 60.1±11.3 years, respectively). Cumulative local tumor progression rates at 6 months, 1 years, 3 years, and 5 years, respectively, were 8.8%,14.8%, 18.9%, and 18.9% in the perivascular group and 8.8%, 13.1%, 15.5%, and 15.5% in the non-perivascular group. The 1-, 3-, 5-, and 10-year overall survival rates, respectively, were 91.3%, 45.6%, 23.9%, and 18.7% in the perivascular group and 88.0%, 47.2%, 27.2%, and 22.6% in the non-perivascular group. No significant between-group differences were detected in cumulative local tumor progression (p=0.567, hazard ratio: 1.224) or overall survival (p=0.801, hazard ratio: 1.047). The major complication rate was 1.0% (1/104, p>0.999) in both groups. Tumor size was the only independent prognostic factor for local tumor progression (hazard ratio: 2.314; p=0.002). On multivariate analysis for overall colorectal liver metastases, tumor diameter >3 cm, tumor location in the right colon, multiple tumors, and extrahepatic metastases before radiofrequency ablation (hazard ratios: 2.046, 1.920, 1.706, and 1.892, respectively; all p<0.001) and intrahepatic recurrence (hazard ratio: 1.564; p=0.002) were associated with poor overall survival. Conclusion: Cumulative local tumor progression, overall survival, and major complications rates did not differ significantly between perivascular and non-perivascular colorectal liver metastases after percutaneous radiofrequency ablation. For perivascular colorectal liver metastases, percutaneous radiofrequency ablation is a safe and effective treatment option.